Interactions between migraine and tension-type headache and alcohol drinking, alcohol flushing, and hangover in Japanese - Yokoyama, Masako (Springer Milan, 2012)
The aim of the study was to investigate associations between headache types and alcohol drinking, alcohol flushing, and hangover. Alcohol consumption is inhibited by the presence of inactive aldehyde dehydrogenase-2 (ALDH2) whose carriers are susceptible to alcohol flushing and hangovers. We conducted a cross-sectional study of the 2,577 subjects (men/women: 1,018/1,559) who reported having ever experienced headaches unrelated to common colds and alcohol hangovers among 5,408 (2,778/2,630) Tokyo health checkup examinees. We used a questionnaire inquiring about current and past facial flushing after drinking a glass of beer which identifies the presence of inactive ALDH2 with a sensitivity and specificity of approximately 90%. Based on ICHD-II criteria migraine was diagnosed in 419 (75/344) subjects, and tension-type headache (TTH) in 613 (249/364). We classified the headaches of the remaining 1,545 (694/851) of headaches sufferers into the category “other headaches (OH)”. The migraineurs drank alcohol less frequently than the subjects with TTH among current/past alcohol flushers and than the subjects with OH regardless of flushing category. No such difference in drinking frequency was observed between TTH and OH. Current/past flushers drank alcohol less frequently than never flushers, and the likelihood that male migraineurs would avoid alcohol drinking than men with TTH or OH was stronger among current/past flushers than among never flushers. Flushers and women were more susceptible to hangover than never flushers and men, respectively, regardless of headache type. Among never flushers, women with migraine were more susceptible to hangover than women with OH. The difference in alcohol sensitivity may partly explain less alcohol consumption by migraineurs.